Spatial distribution and infection rate of leishmaniasis vectors (Diptera: Psychodidae) in Ardabil Province, Northwest of Iran - Eslam Moradi-Asl; Yavar Rassi; Ahmad Ali Hanafi-Bojd; Abedin Saghafipour (Asian Pacific Journal of Tropical Biomedicine, 2019)
Objective: To determine the spatial distribution and infection rate of sand flies as vectors of Leishmania parasite in Ardabil province, northwest of Iran. Methods: This was a descriptive cross-sectional study. The sand flies were collected from 30 areas in all 10 districts of Ardabil province during 2017. The specimens were caught using the sticky traps. The head and genitalia of sand flies were separated and mounted in Berlese solution for microscopic identification. The Geographical Information System ArcMap10.4.1 software was used to provide the spatial maps. Results: A total of 2 794 sand flies specimens were collected and 22 species of sand flies were identified from the two genera: Phlebotomus and Sergentomyia from Ardabil province. The highest frequency was found in Phlebotomus papatasi (23.7%) followed by Phlebotomus kandelakii (13.0%). The promastigote form of Leishmania infantum parasite has been reported from the three main vectors of visceral leishmaniasis (Phlebotomus kandelakii, Phlebotomus perfiliewi and Phlebotomus tobbi) from Ardabil province, where the spatial distribution map of these visceral leishmaniasis vectors was prepared. Some important species of sand flies such as Phlebotomus kandelakii, Phlebotomus perfiliewi and Phlebotomus tobbi were reported and identified as main and probable vectors of visceral leishmaniasis in Ardabil. Conclusions: According to the Geographic Information System based maps, the frequency of the sand flies as leishmaniasis vectors, the leishmania parasite infection rate and the prevalence of the disease in the central areas of Ardabil province are higher than in other areas in Ardabil province.